Comparison of different screening methods for the selection of Ascochyta blight disease on chickpea (Cicer arietinum L.) genotypes - Aydoğan, Abdulkadir (Frontiers in Plant Science, 2024)
Chickpea (Cicer arietinum L.) is the second most important edible food grain legume, widely grown all over the world. However, the cultivation and production of chickpea is mainly affected by the Ascochyta Blight (AB) disease, which causes losses of up to 100% in areas with high humidity and warm temperature conditions. Various screening methods are used in the selection of chickpea genotypes for resistance to AB disease. These methods are Natural Field Condition (NFC), Artificial Epidemic Field Condition (AEC), Marker Assisted Selection (MAS), and Real-Time PCR (RT-PCR). The study was conducted with 88 chickpea test genotypes between the 2014 -2016 growing seasons. The results of the screening were used to sort the genotypes into three categories: susceptible (S), moderately resistant (MR), and resistant (R). Using MAS screening, 13, 21, and 54 chickpea genotypes were identified as S, MR, and R, respectively.For RT-PCR screening, 39 genotypes were S, 31 genotypes were MR and 18 genotypes were R. In the AEC method for NFC screening, 7, 17 and 64 genotypes were S, MR and R, while 74 and 6 genotypes were S and MR, and 8 genotypes were R-AB disease. As a result of screening chickpea genotypes for Ascochyta Blight (AB) disease, it was determined that the most effective method was artificial inoculation (AEC) under field conditions. In the study, Azkan, ICC3996, Tüb-19 and, Tüb-82 were determined as resistant within all methods for Pathotype 1.